Two different allelic mutations in the lecithin-cholesterol acyltransferase gene associated with the fish eye syndrome. Lecithin-cholesterol acyltransferase (Thr123----Ile) and lecithin-cholesterol acyltransferase (Thr347----Met). - Klein, H G (1992)
We have elucidated the genetic defect in a 66-yr-old patient with fish eye syndrome (FES) presenting with severe corneal opacities and hypoalphalipoproteinemia. The patient's plasma concentration of high density lipoprotein (HDL) cholesterol was reduced at 7.7 mg/dl (35.1-65.3 mg/dl in controls) and the HDL cholesteryl ester content was 31% (60-80% in controls); however, total plasma cholesteryl esters were similar to normal (60% of total cholesterol vs. a mean of 66% in controls). The patient's plasma cholesterol esterification rate was slightly reduced at 51 nmol/ml per h (control subjects: 61-106 nmol/ml per h), whereas lecithin-cholesterol acyltransferase (LCAT) activity, assayed using a HDL-like exogenous proteoliposome substrate, was virtually absent (0.9 nmol/ml per h vs. 25.1-27.9 nmol/ml per h in control subjects). DNA sequence analysis of the proband's LCAT gene revealed two separate C to T transitions resulting in the substitution of Thr123 with Ile and Thr347 with Met. The mutation at codon 347 created a new restriction site for the enzyme Nla III. Analysis of the patient's polymerase chain reaction-amplified DNA containing the region of the Thr347 mutation by digestion with Nla III confirmed that the proband is a compound heterozygote for both defects. The patient's daughter, who is asymptomatic despite a 50% reduction of LCAT activity, is heterozygous for the Thr123----Ile mutation. Our data indicate that the regions adjacent to Thr123 and Thr347 of LCAT may play an important role in HDL cholesterol esterification, suggesting that these regions may contain a portion of the LCAT binding domain(s) for HDL.